Penetapan Harga Jual dan Peminat oleh Pedagang serta Hubungannya dengan Fluktuasi Permintaan di Pasar Tradisional MMTC Medan - Marzuti Isra; Cut Zaara Nazwa Shafina; Iskandar Muda Nasution; Dede Fajru Pamungkas; Dimas Setiawan Damanik; Fathur Rahman Hasibuan; Ariq Ahmad Fauzan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the determination of selling prices and enthusiasts by traders and their relationship with demand fluctuations in the traditional market of MMTC Medan. The method used is a qualitative descriptive analysis method with a survey approach, involving three traders, namely rice, onion, and cabbage traders, data collected through direct interviews. The results of the study show that the setting of selling prices by traders has an effect on market enthusiasts as well as fluctuations in demand. Merchants set prices based on a combination of cost of goods sold, competitor prices, and estimated consumer purchasing power. Significant price fluctuations tend to lower the volume of demand, especially in non-primary products, and also poor quality of goods. Thus, this study concludes that understanding demand patterns and price adaptability are the main key factors in maintaining the business continuity of traders in the traditional market of MMTC Medan.